Verification of Management Representations: A First Step Toward Independent Audits of Management. - Robertson, Jack C.; Clarke, Robert W. (The Accounting Review, 1971)
Abstract The article focuses on management representation as the first step towards independent audits of management. Economist Robert W. Clarke developed a rational case for extension of the Certified Public Accountant (CPA's) attest function in corporate annual reports' and economists Harold Q. Langenderfer and Jack C. Robertson presented a theoretical structure for independent audits of management. These authors pointed out the demand for additional information about management and managerial activities and suggested forms of attest extension and management auditing as potential approaches for satisfying this demand. Langenderfer-Robertson perceived management auditing in the context of independent audits of management representations in relation to the widely accepted use of the term management audit to describe evaluations or audits for management. According to Clarke, the term independent audits of management representations was used to connote an attestation context of auditing whereby credibility is added to the representations made by one party to another through the expert opinion of an independent third party.